World development report 1982 - World Bank. (Washington, DC : World Bank, 1982)
The publications examine problem associated with low-income countries where bulk of poverty is concentrated. The report uses the world bank experience and country illustrations to highlights some institutional issues involved in stimulating more rapid agricultural development.
Some vols. have also a distinctive titles.
nif 26/04/13, ijb 19/02/2019 , osa 05/03/19
Loans
Keywords: Economic development; Agriculture